Sexual Assertiveness Across Cultures, Genders, and Sexual Orientations: Validation of the Short Sexual Assertiveness Questionnaire (SAQ-9) - Nagy, Léna; Koós, Mónika; Kraus, Dr Shane W; Demetrovics, Zsolt; Potenza, Marc N; Ballester-Arnal, Rafael; Batthyány, Dominik; Bergeron, Sophie; Billieux, Joël; Briken, Peer; Burkauskas, Julius; Cárdenas-López, Georgina; et al. (Assessment, 2025)
Sexual assertiveness (SA) is an important concept in understanding sexual well-being and decision-making. However, psychometric evaluation of existing measures of SA in diverse populations is largely lacking, hindering cross-cultural and comparative studies. This study validated the short version of the Sexual Assertiveness Questionnaire (SAQ-9) and examined its measurement invariance across several languages, countries, genders, sexual orientations, and relationship statuses among 65,448 sexually-active adults (Mage = 32.98 years, SD = 12.08, 58% women, 2.74% gender-diverse individuals) taking part in the International Sex Survey. The scale demonstrated adequate psychometric properties. Measurement invariance tests indicated that the SAQ-9 is suitable for comparing individuals from different cultures, genders, sexual orientations, and relationship statuses, and significant group differences were also noted (e.g., gender-diverse individuals reported the highest levels of SA). Findings suggest that the SAQ-9 is a reliable and valid measure of SA and appropriate for use in diverse populations, with specific populations exhibiting varying levels of SA.
Keywords: International Sex Survey (ISS); sexual and gender minorities; cross-cultural; gender difference; validation; sexual assertiveness; SAQ-9